An alternative synthesis of (+) - propranolol and (+) atenolol - Inkum R. (2014)
Herein, a simple synthesis pathway of beta-blockers starting from allyl amine is presented. This synthesis features the opening of an epoxide ring with phenol derivatives followed by N-alkylation with iso-propylbromide to produce racemic propranolol and atenolol. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.